Twenty Years - Oldshue, Robert (Ars Medica, 2014)
A writing teacher once told me that he'd written (and sold) a half dozen articles, all different but all about the same event. He said that a teenaged girl had been injured in a car accident and had lain comatose in the hospital for several months before recovering.